Comprehensive planning and the role of SDSS in flood disaster management in Malaysia - Billa, Lawal; Shattri, Mansor; Mahmud, Ahmad Rodzi; Ghazali, Abdul Halim (Emerald, 2006)
Purpose – To present a comprehensive flood management plan for Malaysia, the various planning stages and the proponents of the plan. It is also to expound and highlight the importance of spatial information technology in the strategy and to outline the critical decision-making at various levels of the plan.